Bringing the rain to Kapiti Plain - Aardema, Verna; Vidal, Beatriz (New York : Dial Press, 1981)
A cumulative rhyme relating how Ki-pat brought rain to the drought-stricken Kapiti Plain.
Accelerated Reader AR
Keywords: Droughts -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Africa -- Juvenile fiction